Associations of carbohydrate quality and cardiovascular risk factors vary among diabetes subtypes - Katharina S. Weber; Sabrina Schlesinger; Janina Goletzke; Klaus Straßburger; Oana-Patricia Zaharia; Sandra Trenkamp; Robert Wagner; Wolfgang Lieb; Anette E. Buyken; Michael Roden; Christian Herder; for the GDS group (Cardiovascular Diabetology)
Abstract Background Assess the intake of carbohydrate quality and their association with cardiovascular risk factors among diabetes subtypes. Methods Participants of the German Diabetes Study (GDS) (recent-onset diabetes (n = 487) and 5-years thereafter (n = 209)) were allocated into severe autoimmune diabetes (SAID, 35%), severe insulin-deficient diabetes (SIDD, 3%), severe insulin-resistant diabetes (SIRD, 5%), mild obesity-related diabetes (MOD, 28%), and mild age-related diabetes (MARD, 29%). Dietary glycemic index (GI), glycemic load (GL), and intake of higher- (≥ 55) and low-GI (< 55) foods, dietary fiber, and total sugar were derived from a validated food frequency questionnaire and cross-sectionally associated with cardiovascular risk factors (blood lipids, subclinical inflammation, blood pressure, fatty liver index) using multivariable linear regression analysis for subtypes with prevalences ≥ 10%. Results Intake of carbohydrate quality parameters was broadly comparable between the subtypes. Among SAID higher total sugar intake was associated with lower HDL-cholesterol (ß (95% CI) relative change per 1 SD increment: − 3.4% (− 6.7; − 0.1)). No clear associations were seen among MOD. Among MARD, a higher dietary GL and higher-GI carbohydrate intake were associated with higher serum triglycerides (10.9% (2.4; 20.1), 12.4% (3.9; 21.5)) and fatty liver index (absolute change: 0.18 (0.06; 0.31), 0.17 (0.05; 0.28)) and lower HDL-cholesterol (− 4.1% (− 7.6; − 0.4), − 4.4% (− 7.8; − 0.8)), whilst higher intake of low-GI carbohydrates and dietary fiber were associated with lower high-sensitivity C-reactive protein (− 16.0% (− 25.7; − 5.1), − 13.9% (− 24.2; − 2.2)). Conclusions Associations of carbohydrate quality parameters with blood lipids, subclinical inflammation, and fatty liver index differed between diabetes subtypes. However, evidence is too preliminary to derive subtype-specific recommendations. Trial registration Clinicaltrials.gov: NCT01055093.